Catenarin Prevents Type 1 Diabetes in Nonobese Diabetic Mice via Inhibition of Leukocyte Migration Involving the MEK6/p38 and MEK7/JNK Pathways. (13th February 2012) - Shen, Ming-Yi; Lin, Yu-Ping; Yang, Bei-Chang; Jang, Yu-Song; Chiang, Chih-Kang; Mettling, Clément; Chen, Zeng-Weng; Sheu, Joen-Rong; Chang, Cicero L.; Lin, Yea-Lih; Yang, Wen-Chin
Abstract : Inflammation contributes to leukocyte migration, termed insulitis, and β -cell loss in type 1 diabetes (T1D). Naturally occurring anthraquinones are claimed as anti-inflammatory compounds; however, their actions are not clear. This study aimed to investigate the effect and mechanism of catenarin on the inflammatory disease, T1D. Catenarin and/or its anthraquinone analogs dose-dependently suppressed C-X-C chemokine receptor type 4 (CXCR4)- and C-C chemokine receptor type 5 (CCR5)-implicated chemotaxis in leukocytes. Catenarin, the most potent anthraquinone tested in the study, prevented T1D in nonobese diabetic mice. Mechanistic study showed that catenarin did not act on the expression of CCR5 and CXCR4. On the contrary, catenarin inhibited CCR5- and CXCR4-mediated chemotaxis via the reduction of the phosphorylation of mitogen-activated protein kinases (p38 and JNK) and their upstream kinases (MKK6 and MKK7), and calcium mobilization. Overall, the data demonstrate the preventive effect and molecular mechanism of action of catenarin on T1D, suggesting its novel use as a prophylactic agent in T1D.